Analisis Manajemen Risiko Pembiayaan Modal Kerja (PMK) Pada Bank BJB Syariah Kantor Cabang Pembantu Lippo Cikarang - Nita Muhaini Saputri TQ; Isfandayani - (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
BJB Sharia Bank is the one of the banks that taking role in capital participation, capital financialworkings is a product that very potentially risking. If it doesn’t handle correctly, it will cause lossesthat should be gotten by the BJB Sharia Bank, for that these should need a risk management. Thisanalyze aims for determining the types of risks and how the implementation of risk managementfor Capital Financial Working contained in BJB Sharia Bank Lippo Cikarang Sub Branch in termsof identification risk, measurement risk, monitoring risk and controlling risk. In this study using aqualitative descriptive method. Data retrieval is done by observation, interviews and documentationto four sources of informants BJB Sharia Bank Lippo Cikarang Sub Branch. Data analysis will bedone by doing three steps, they are; data reductions, data display, and verification from that analysisdata result by evidencing the validity of data through source triangulation techniques. The observationresult shows that the faced risk by BJB Sharia Bank Lippo Cikarang Sub Branch are financing riskand law risk. From the identification results, BJB Sharia Bank Lippo Cikarang Sub Branch will beface operational risk, liquidity risk, strategic risk, investment risk, reputation risk, compliance risk,and yield risk also. In application, management risk uses four steps, they are; identification risk,assessment risk, monitoring risk, and controlling risk. From that management risk application, BJBSharia Bank Lippo Cikarang Sub Branch has been able to minimize the impact of faced risk by capitalfinancial working.